Neural Responses to a Putative Set‐shifting Task in Children with Autism Spectrum Disorder. Issue 9 (25th August 2020) - Dirks, Bryce; Romero, Celia; Voorhies, Willa; Kupis, Lauren; Nomi, Jason S.; Dajani, Dina R.; Odriozola, Paola; Burrows, Catherine A.; Beaumont, Amy L.; Cardona, Sandra M.; Parlade, Meaghan V.; Alessandri, Michael; et al.
Abstract : While much progress has been made toward understanding the neurobiology of social and communication deficits associated with autism spectrum disorder (ASD), less is known regarding the neurobiological basis of restricted and repetitive behaviors (RRBs) central to the ASD diagnosis. Symptom severity for RRBs in ASD is associated with cognitive inflexibility. Thus, understanding the neural mechanisms underlying cognitive inflexibility in ASD is critical for tailoring therapies to treat this understudied yet pervasive symptom. Here we used a set‐shifting paradigm adopted from the developmental cognitive neuroscience literature involving flexible switching between stimulus categories to examine task performance and neural responses in children with ASD. Behaviorally, we found little evidence for group differences in performance on the set‐shifting task. Compared with typically developing children, children with ASD exhibited greater activation of the parahippocampal gyrus during performance on trials requiring switching. These findings suggest that children with ASD may need to recruit memory‐based neural systems to a greater degree when learning to flexibly associate stimuli with responses. Lay Summary: Children with autism often struggle to behave in a flexible way when faced with unexpected challenges. We examined brain responses during a task thought to involve flexible thinking and found that compared with typically developing children, those with autism relied more on brain areas involved in learning and memory to complete the task. This study helps us to understand what types of cognitive tasks are best suited for exploring the neural basis of cognitive flexibility in children with autism. Autism Res 2020, 13: 1501–1515 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.